DYNAMIC DISCOVERY OF NETWORK FUNCTIONS IN MOBILITY INTERWORKING ACROSS RADIO ACCESS TECHNOLOGIES (2022)
Aspects of the subject disclosure may include, for example, a machine-readable medium, comprising executable instructions that, when executed by a processing system including a processor, facilitate performance of operations including receiving a first message from a mobile management entity (MME) in a Long-Term Evolution (LTE) network indicating a handover of user equipment (UE) to a fifth generation (5G) network covering a first area in which the UE is located; discovering an access mobility management function (AMF) in the 5G network responsive to the second message; receiving a second message from the AMF indicating a handover of the UE to the LTE network; and discovering a second mobile management entity (MME) in the LTE network covering a second area in which the UE is located. Other embodiments are disclosed.